Understanding and Promoting Mental Health of High School Students: An Lgbt Perspective in an Educational Environment - Rika Amran; Erdanela Setiowati (PT. Anagata Sembagi Education, 2024)
This activity aims to explore and understand the mental health of high school students with a focus on the LGBT perspective in the educational environment of SMA 2 Adabiah Padang. The research method involves lectures and discussions followed by a question and answer session. Evaluation results demonstrate an improvement in participants' understanding post-counseling, indicating the success of this method in enhancing awareness of LGBT issues and adolescent mental health. This intervention significantly contributes to enhancing understanding and support for adolescent mental health in the educational setting